2019
DOI: 10.1002/alr.22479
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette smoke extract inhibits cell migration and contraction via the reactive oxygen species/adenosine monophosphate–activated protein kinase pathway in nasal fibroblasts

Abstract: Background Fibroblast migration plays a significant role in wound healing after endoscopic sinonasal surgery. Cigarette smoke extract (CSE) is a potent inhibitor of fibroblast functions including cell proliferation and migration. The purpose of the study was to determine the influence of CSE on migration and collagen gel contraction in nasal fibroblasts and investigate its underlying mechanisms. Methods Fibroblast migration was evaluated using wound healing assay and transwell migration assay. Contractile acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 24 publications
(52 reference statements)
0
10
0
Order By: Relevance
“…Smoking has long been believed to be harmful to wound healing since habitual smokers have higher rates of postsurgical complications such as infections, wound dehiscence, and tissue necrosis. 97,98 Moreover, there are multiple studies showing that smoking affects all phases of wound healing: it increases thrombus formation, 99,100 impairs the phagocytic and bactericidal activity of inflammatory cells, 101,102 inhibits fibroblast migration, 103 and reduces collagen deposition. 104 The mechanisms underlying these observations may involve but are not confined to the fact that smoking produces excessive levels of reactive oxygen species 103 and induces vitamin C deficiency.…”
Section: Effect Of Smokingmentioning
confidence: 99%
“…Smoking has long been believed to be harmful to wound healing since habitual smokers have higher rates of postsurgical complications such as infections, wound dehiscence, and tissue necrosis. 97,98 Moreover, there are multiple studies showing that smoking affects all phases of wound healing: it increases thrombus formation, 99,100 impairs the phagocytic and bactericidal activity of inflammatory cells, 101,102 inhibits fibroblast migration, 103 and reduces collagen deposition. 104 The mechanisms underlying these observations may involve but are not confined to the fact that smoking produces excessive levels of reactive oxygen species 103 and induces vitamin C deficiency.…”
Section: Effect Of Smokingmentioning
confidence: 99%
“…In the presence of water, airborne smoke rapidly degrades, releasing high quantities of ROS (25). Moreover, cigarette smoke exposure inhibits cell migration and collagen contraction activity in nasal fibroblasts through the ROS/ AMPK signaling pathway (26).…”
Section: Oxidative Stressmentioning
confidence: 99%
“…The production of a large amount of ROS is one of the most important reasons that tobacco products affect the phenotype of fibroblasts. Previous reports showed that oxidative stress caused by tobacco product in human lung, gingival or nasal fibroblasts are thought to contribute a lot in attenuates collagen gel contraction and wound healing [ 15 , 22 , 23 ]. Shin et al showed that ROS/AMPK is the downstream signal pathway respond to oxidative stress caused by tobacco products [ 22 ].…”
Section: The Effect Of Tobacco Product On Fibroblastsmentioning
confidence: 99%
“…Previous reports showed that oxidative stress caused by tobacco product in human lung, gingival or nasal fibroblasts are thought to contribute a lot in attenuates collagen gel contraction and wound healing [ 15 , 22 , 23 ]. Shin et al showed that ROS/AMPK is the downstream signal pathway respond to oxidative stress caused by tobacco products [ 22 ]. The use of antioxidants can remarkably promote proliferation and migration on human fibroblasts [ 24 ].…”
Section: The Effect Of Tobacco Product On Fibroblastsmentioning
confidence: 99%